THE IMPLEMENTATION OF KAMPUS MENGAJAR PROGRAM IN MUSIC ARTS LEARNING: A QUALITATIVE STUDY AT AN ELEMENTARY SCHOOL IN MINAHASA, SULAWESI UTARA - Kaunang, Meyny S. C. (SoCul: International Journal of Research in Social Cultural Issues, 2024)
Kampus Mengajar is one of the programs proposed by the Ministry of Education, Culture, Research, and Technology of Indonesia as part of the implementation of Kurikulum Merdeka in Higher Education Institution. This program is expected to help the students to learn outside the campus to hone their problem-solving skills by becoming the partner of the teacher at the designated elementary school. The present study aims to investigate the implementation of Kampus Mengajar on music arts learning at elementary school. This qualitative study is conducted at an elementary school in Minahasa, Sulawesi Utara. Observation, interviews and documentation are used by the researcher to collect the data. The data obtained are analyzed using the interactive qualitative data analysis. The findings show that the music arts learning at the elementary school get many benefits because of the implementation of Kampus Mengajar Program. The students participated in this program helped the teacher by assisting them during the learning process, providing a novel perspective to the teacher regarding the teaching of music arts. It benefited the teacher since they can gain new understanding related to the teaching of music arts. The students at the elementary school can also learn in more engaging way. Hence, the implementation of Kampus Mengajar contributes positively to the teaching and learning process of music arts in elementary school.